Effect of Snakehead Fish and Sea Cucumber Extract Administration on Mast Cell Infiltration, Interlukin-6 (IL-6), and Albumin Levels in Burns and Surgical Wounds - Purwoko, Purwoko; Putro, Bambang Novianto; Hananto, Arif Zuhal Amin (Faculty of Medicine-Universitas Airlangga, 2022)
Introduction: Burn injury impairs almost every organ system, which causes significant morbidity and mortality. Meanwhile, the phases included in burn healing are inflammation, cell recruitment, matrix deposition, epithelialization, and tissue remodeling phase. Previous studies showed that snakehead fish and sea cucumber extract have these effects and are beneficial in burn and post-surgery wounds. Objective: This study aims to analyze the effect of snakehead fish and sea cucumber extract supplementation towards mast cell infiltration, IL-6, and albumin level in burn and post-surgery wounds. Methods: A double-blind randomized control trial was carried out at Dr. Moewardi Hospital Surakarta in November 2017 on 30 subjects, which were divided into 2 groups. Mast cell infiltration was observed on burn and post-surgery wounds colored with Toluidine Blue, while IL-6 and albumin were measured -blood, where both groups had comparable basic characteristics. Results: There was a statistically insignificant (p=0.835) higher increase in albumin level in the treatment group, while an insignificant (p=0.056) greater decrease also occur in the IL-6 level. The decrease in cell mast infiltration after treatment was also higher and not statistically significant (p=0.526). Previous studies showed that amino acids from snakehead fish play an important role in wound healing. Meanwhile, high EPA content in sea cucumber is due to its ability as an Echinodermata to regenerate tissue. It was also discovered that the results available about sea cucumber and sea snake extract on wound healing are different based on the skin condition after the use of the extracts. Conclusion: Snakehead fish and sea cucumber extract supplementation can increase albumin level, decrease IL-6 level and mast cell infiltration in burn or post-surgery wounds.